(untitled) (Journal of Medicine, 2009)
Poisoning and snakebite are commonly encountered emergency situation in Bangladesh. Morbidity per annum reported from static primary health care set up and district hospitals following poisoning are 0.56% of total morbidity. Reports published from the DGHS in 2001 recorded poisoning as fifteenth cause of morbidity & second commonest cause of death second to acute respiratory tract infection (1956). Common poisoning encountered in the community include pesticide poisoning, kerosene poisoning, poisoning by unknown sedative substances for stupefying purpose and with occasional reports of methanol poisoning, aluminium phosphide poisoning, copper sulphate poisoning and puffer fish poisoning. A change in the trends of poisoning particularly âtravel related’ poisoning by sedatives instead of previously used âDhatura’ have been found in the country. Â doi:10.3329/jom.v10i3.2010 J Medicine 2009; 10 (Supplement 1): 15-17